The Mediation Role of Career Calling: Family-Supportive Supervisor Behaviors (FSSBs) and Life Satisfaction - Joko Fitro (International Journal of Applied Business and International Management, 2024)
One of the police's duties is to serve and protect the community despite facing various obstacles such as superior support and career calling which can ultimately determine life satisfaction. Therefore, this study aims to analyze the impact of Family-Supportive Supervisor Behaviors (FSSBs) on police officers' life satisfaction and career calling and to assess career calling as a mediator in this relationship. The population in this study were police personnel working in North Maluku province. Purposive sampling was used to select the sample of this study. A total of 132 samples were lower and middle-level officers involved in this study. The analytical tool used to test the hypothesis in this study was hierarchical regression. Based on the results of the hypothesis testing, it was shown that career calling fully mediated the relationship between FSSBs and life satisfaction. The results confirm that FSSBs significantly enhance police officers' life satisfaction and career calling. Career calling also positively influences life satisfaction and fully mediates the relationship between supervisory support and life satisfaction. These findings highlight the importance of supportive leadership in fostering career development and overall well-being among police personnel.